CFD investigation of a 3.5 stage transonic axial compressor including real geometry effects - Persson, Anton; Runsten, Josef (My University, 2011)
When designing a transonic multi-stage compressor it is desirable to keep the devel- opment cost low and development time short while finding the optimal geometry for a given function. In order to keep the cost down CFD analysis can be used together with an optimization tool instead of expensive experiments. In the CFD optimization process, a relatively coarse mesh based on a simplified geometric definition is normally used in order to screen the design space in a reasonably short time. Once a preliminary design is set, CFD analysis using a higher fidelity model is desired to verify that the design fulfill the performance requirements. A higher fidelity model normally includes features such as fillets at the blade root section and the clearance height between the rotor tip and the casing. The computational domain should be highly resolved especially in the near wall regions. In this project the geometry of a cold rotor blade is transformed into the shape of a blade in operating condition, by applying displacements due to centrifugal and thermal loadings and surface deviations from the manufacturing process. This is done by applying displacements of the geometry from FE-analyses which account for rotational and thermal effects together with measured surface nonconformance data originated from a manufactured geometry. An interpolation method utilizing radial basis functions is developed. With the available data in this project, the developed routine performs well in the cold to hot transformation of the rotor blade. However, the results are less reliable for the nonconformance case. During the European 6th framework VITAL research programme a 3.5 stage tran- sonic axial compressor was developed and tested. CFD simulations that have been carried out has shown great disagreement in performance over the second rotor, compared to the experimental data. The second rotor blade of this compressor is in this thesis analysed with real geometry effects using Ansys CFX. The lack of fillets and tip clearance in the design geometry clearly affects the passage area and thus the mass flow capability. The pressure rise is lower for the hot blade, giving a lower polytropic efficiency. A further reduction of passage area due to nonconformances yield a further decrease in mass flow.
Keywords: Energi; Hållbar utveckling; Strömningsmekanik; Energy; Sustainable Development; Fluid mechanics